Microstructural evolution and thermal stability of Fe–Zr metastable alloys developed by mechanical alloying followed by annealing. Issue 25 (1st September 2016) - Sooraj, S.; Muthaiah, V. M. Suntharavel; Kang, P. C.; Koch, Carl C.; Mula, Suhrit
Abstract: The effect of Zr (up to 1 at.%) addition on the formation of Fe–Zr metastable alloys and their thermal stability were investigated for their possible nuclear applications. Fe– x Zr ( x  = 0.25, 0.5, 1%) alloys were synthesised by mechanical alloying under a high-purity argon atmosphere using stainless steel grinding media in a SPEX 8000M high energy mill. The milling was conducted for 20 h with a ball-to-powder weight ratio of 10:1. The formation of metastable solid solutions after milling was confirmed from the change in the Gibbs free energy analysis as per Miedema's model. The microstructural characterisation was carried out by analysis of X-ray diffraction, atomic force microscopy and transmission electron microscopy. The effect of Zr on the thermal stability of Fe–Zr alloys was investigated by extensive annealing experiments followed by microstructural analysis and microhardness measurements. The stabilisation was found to occur at 800 °C and thereafter, no significant change in the crystallite size was observed for the samples annealed between 800 and 1200 °C. The supersaturated solid solution, especially 1% Zr alloy, found to be highly stable up to 800 °C and the microhardness value of the same measured to be as high as 8.8 GPa corresponding to a crystallite size of 57 nm. The stabilisation effect has been discussed in the light of both the thermodynamic and kinetic mechanisms and the grain size stabilisation is attributed to the grain boundary segregation of Zr atoms and/or Zener pinning by nanoscale precipitation of the Fe2 Zr phase.